Studies on Rainfall Characteristics in Chambal Catchment - Handa, D. P.; Niwas, Shri; Kaybri, M. L. (Indian Forester, 1979)
Rainfall characteristics of the Chambal catchement were studied. Wide and irregular variations in the total number of ralay days were observed over the catchment. Frequency of maximum twenty four hours rainfall was also worked out. It varies from 85 mm to 323 mm in the catchment.